Design of a Custom RT-qPCR Array for Assignment of Abiotic Stress Tolerance in Traditional Portuguese Grapevine Varieties - Carvalho, Luísa C.; Silva, Marília; Coito, João L.; Rocheta, Margarida P.; Amâncio, Sara (Frontiers in Plant Science, 2017)
Widespread agricultural losses attributed to drought, often combined with high temperatures, frequently occur in the field, namely in Mediterranean climate areas, where the existing scenarios for climate change indicate an increase in the frequency of heat waves and severe drought events in summer. Grapevine (Vitis vinifera L.) is the most cultivated fruit species in the world and the most valuable one and is a traditional Mediterranean species. Currently, viticulture must adjust to impending climate changes that are already pushing vine-growers toward the use of ancient and resilient varieties. Portugal is very rich in grapevine biodiversity, however, currently, 90% of the total producing area is planted with only 16 varieties. There is a pressing need to understand the existing genetic diversity and the physiological potential of the varieties/genotypes available to be able to respond to climate changes. With the above scenario in mind, an assembly of 65 differentially expresses genes (DEGs) previously identified as responsive to abiotic stresses in two well studied genotypes, ‘Touriga Nacional’ and ‘Trincadeira,’ was designed to scan the gene expression of leaf samples from 10 traditional Portuguese varieties growing in two regions with distinct environmental conditions. Forty-five of those DEGs proved to be associated to “abiotic stress” and were chosen to build a custom qPCR array to identify uncharacterized genotypes as sensitive or tolerant to abiotic stress. According to the experimental set-up behind the array design these DEGs can also be used as indicators of the main abiotic stress that the plant is subjected and responding to (drought, heat, or excess light).